In situ assessment of terrestrial gamma radiation dose and associated radiological hazards in Katsina State, Nigeria - Garba, Nuraddeen Nasiru; Abdulkadir, Mukhtar; Nasiru, Rabiu; Saleh, Muneer Aziz; Bello, Suleiman; Khandaker, Mayeen Uddin *; Che Abdullah, Che Azurahanim; Kankara, Usman Musa (Taylor and Francis Group, 2023)
Terrestrial gamma radiation dose (TGRD) rates were measured in situ from different locations in Katsina State, Nigeria, using a portable radiation survey metre based on geological formations and soil types. The measured TGRD rates ranged from 45 to 271 nGyh–1 with an average value of 116 ± 1 nGyh–1. Geological formation (silicified sheared rock) and soil type (lithosols and ferruginous crusts and ferruginous tropical soils) appeared to have the highest mean TGRD values of 163 and 134 nGyh–1 with sandstone geological formation and alluvial and hydromorphic soils having the lowest TGRD with values of 80 and 61 nGyh–1, respectively. One way ANOVA results shows that the tested null hypothesis was rejected. Thus, indicating that there exists a strong relationship between the various geological formations, soil types with the measured TGRD values based on the alternate hypothesis. Human health hazard indices like annual effective dose equivalent (AEDE), lifetime outdoor annual equivalent dose, and relative excess lifetime outdoor cancer risk associated with the mean TGRD of the study area were also calculated and found to be 0.711, 9.955 mSv, and 5.79 × 10–4, respectively. These values were higher than the world average values but favourable compared with the safety limits recommended by ICRP.